Thermal comfort and energy in residential buildings in a cold climate - Lundqvist, Petter (Luleå tekniska universitet, Energivetenskap, 2023)
Building design typically has a focus on energy use and economy. The indoor environment is often overlooked or simplified to such an extent that essential aspects are neglected. Additionally, introducing technologies for improving energy efficiency can also affect the indoor thermal climate and, in turn, the perceived indoor comfort. Furthermore, an energy efficiency measure which creates discomfort could end up ineffective due to occupant behaviour. The main objective of this thesis is to demonstrate why indoor thermal comfort is vital to consider during building design or renovation procedures. It also explores some methods for improving the sub-Arctic region related to this matter. In this thesis, six different residential buildings have been studied within the northernmost region of Sweden—Norrbotten. This region is sub-Arctic, with long, cold and dark winters. The summers are brief but bright and relatively warm. In this thesis, the winter cases are in focus, but summer cases are also assessed to a minor degree. Both energy usage and indoor thermal climate parameters were measured throughout the buildings. The results indicate a need to assess implemented energy efficiency measures. The results also show the importance of considering the indoor thermal climate during energy efficiency measures. The thesis also discusses the use of the popular building performance simulation (BPS) software package IDA ICE. The software package performed well when calculating and predicting energy use and balance. However, IDA ICE could not detect certain indoor thermal climate problems. In these cases, some surface temperatures were incorrect in IDA ICE models, where warm radiator surfaces were the most evident. The error led to the radiation temperatures being too low, affecting thermal comfort parameters such as the predicted percentage of dissatisfied (PPD). The error could give a false impression of thermal comfort. Computational fluid dynamics (CFD) simulations can acquire more accurate radiation temperatures. With a ...